Management of radiodermatitis in cancer patients: integrative review (Research, Society and Development, 2020)
A radiodermatitis directly affects the quality of life of patients undergoing radiotherapy for pain, and local and systemic may occur in some cases. Because they are complex wounds that are difficult to heal, such as cutaneous wounds due to radiodermatitis, they can have repercussions, with social and personal stigma, due to changes in body image, especially in cases of those who radiate regions such as the head, neck and breasts. The present study aimed to verify the scientific evidence and evidence for the management of radiodermatitis in patients with cancer, in national and international literature. This is an integrative review study with five scientific articles selected in the last ten years, using the Virtual Health Library database. Three publications evaluated with a descriptive and cross-sectional design, in which questionnaires were answered about the nurse's performance in relation to the management of radiodermatitis. The need to use evaluation scales for the characterization of radiation-induced toxicity and the development of standards to promote improvements in care practice with standardization of conduct, based on scientific evidence, was highlighted. It was found that this integrative review did not have, among the analyzed publications, any product that started in the topical management of radiodermatitis. The need to carry out further experimental studies such as clinical, randomized, controlled and multicenter trials to support an evidence-based practice is emphasized.